Pengamanan Terpadu dalam Pencegahan Keberangkatan Pekerja Migran Indonesia Ilegal di Perbatasan Entikong Kalimantan Barat - Alunaza, Hardi; Ilmah, Daris Nurul (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 1 (2024): ISU-ISU PEMBANGUNAN, 2024)
The increase in cases of Indonesian migrant workers illegally made the government carry out various handling regulations. This study uses a qualitative descriptive approach and interview data collection techniques. This research aims to examine more deeply about integrated security efforts in preventing the illegal departure of Indonesian Migrant Workers carried out by the Indonesian government, especially the West Kalimantan government. This research is divided into four discussions, namely the increase in illegal Indonesian Migrant Workers, the problem of illegal Indonesian Migrant Workers in Entikong, regulations carried out by the Indonesian National Army (TNI) and BP2MI, and analysis of PMI problems from the perspective of Human Security. The final results obtained in this study show that the performance carried out by the government is related to this illegal PMI problem, especially the TNI and BP2MI are trying to maximize performance to secure national security from illegal activities that endanger the country.